A flexible Sb2O3/carbon cloth composite as a free-standing high performance anode for sodium ion batteries. Issue 98 (27th November 2017) - Fei, Jei; Cui, Yali; Li, Jiayin; Xu, Zhanwei; Yang, Jun; Wang, Ruiyi; Cheng, Yayi; Hang, Jianfeng
Abstract : A flexible Sb2 O3 /carbon cloth (CC) composite is synthesized using a simple solvothermal method. Abstract : A flexible Sb2 O3 /carbon cloth (CC) composite is synthesized using a simple solvothermal method. The Sb2 O3 /CC composite exhibits higher capacity and capacity retention of alloying and conversion reactions as an anode for sodium ion batteries, attributed to the good conductivity of CC and strong chemical bonds between Sb2 O3 and CC.